Strategic Operational Management in Regional Development: Analyzing the Efficiency and Effectiveness of Public Fiscal Policies in Banyumas, Indonesia - Cabase, Daniar Casta; Raharjo, Raden Johnny Hadi (International Journal of Scientific Research and Management (IJSRM), 2024)
This research examines the strategic operational management of public fiscal policies and their impact on regional development in Banyumas, Indonesia. By analyzing the efficiency and effectiveness of the Regional Revenue and Expenditure Budget (RPP) and its influence on the Gross Regional Domestic Product (PDRB), this study aims to identify key strategic factors that enhance regional economic performance. Utilizing advanced statistical models and operational efficiency metrics, the study provides a comprehensive evaluation of how strategic fiscal management can drive sustainable regional growth. Operational management and strategic planning play pivotal roles in determining the efficiency and effectiveness of public fiscal policies, particularly in the context of regional development. This research seeks to investigate these dynamics within the Banyumas region of Indonesia, focusing on how strategic operational management of the Regional Revenue and Expenditure Budget (RPP) influences economic growth as measured by the Gross Regional Domestic Product (PDRB).